Inovasi Model Pembelajaran Geografi Melalui Teaching at The Right Level Untuk Meningkatkan Critical Thinking dan Problem Solving pada Kurikulum Merdeka - Desfandi, Mirza; Zalmita, Novia; Furqan, M Hafizul; Muridha, Nabila (Jurnal Sosioteknologi, 2025)
Critical thinking and problem solving are skills needed by students to deal with the complexity and ambiguity of information. The teaching at the right level (TaRL) approach is a learning approach that orients students to learn in a learning design based on ability levels. The implementation of the Kurikulum Merdeka (Independent Curriculum) is one of the efforts aimed at developing students' character as well as their critical thinking and problem-solving skills. The purpose of this study is to develop a geography learning model that utilizes the teaching at the right level approach to enhance critical thinking and problem-solving skills within the framework of the Independent Curriculum. This research method uses research and development, using a 4D development model (four-D model) with stages, namely, define, design, develop, and disseminate. The subjects of this study included validators, who were geographylecturers and teachers, as well as students from SMA Negeri 2 and SMA Negeri 7 in Banda Aceh. Data collection techniques used feasibility test sheets, tests, and questionnaires, which were analyzed with N-gain. Research Results: At the defining stage, the division of heterogeneous student groups made it difficult for teachers to develop students' critical thinking skills. The designing stage consisted of designing teaching modules, student worksheets, and assessment instruments. The development stage, expert validation, content, and construction of the developed model fall into the category of highly feasible implementation. During the dissemination stage, student N-gain increased by 50% in the medium category and by 23.3% in the high category. Student responses to the learning model were in the very good category, with a percentage of 93.8%.